FORS spectroscopy of galaxies in the Hubble Deep Field-South - Rigopoulou, D; Vacca, W; Berta, S; Franceschini, A; Aussel, H (2005)
We present low resolution multi-object spectroscopy of an I-band magnitude limited (IAB ≃ 23-23.5) sample of galaxies located in an area centered on the Hubble Deep Field-South (HDFS). The observations were obtained using the Focal Reducer/low dispersion Spectrograph (FORS) on the ESO Very Large Telescope. Thirty-two primary spectroscopic targets in the HST-WFPC2 HDFS were supplemented with galaxies detected in the Infrared Space Observatory's survey of the HDFS and the ESO Imaging Deep Survey to comprise a sample of 100 galaxies for spectroscopic observations. Based on detections of several emission lines, such as [OII]λ3727, Hβ and [OIII]λ5007, or of other spectroscopic features, we measured accurate redshifts for 50 objects in the central HDFS and flanking fields. The redshift range of the current sample of galaxies is 0.6-1.2, with a median redshift of 1.13 (at I ≃ 23.5 not corrected for completeness). The sample is dominated by starburst galaxies with only a small fraction of ellipticals (∼ 10%). For the emission line objects, the extinction corrected [OII]λ3727 line strengths yield estimates of star formation rates in the range 0.5-30 M⊙yr-1. We used the present data to derive the [OII]λ3727 luminosity function up to redshift of 1.2. When combined with [OII]λ3727 luminosity densities for the local and high redshift Universe, our results confirm the steep rise in the star formation rate (SFR) to z ≃ 1.3. © ESO 2005.